A pragmatic dementia risk score for patients with mild cognitive impairment in a memory clinic population: Development and validation of a dementia risk score using routinely collected data - Meng Wang; Tolulope T. Sajobi; Zahinoor Ismail; Dallas Seitz; Thierry Chekouo; Nils D. Forkert; Karyn Fischer; Aaron Mackie; Dawn Pearson; David Patry; Alicja Cieslak; Bijoy Menon; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction This study aimed to develop and validate a 3‐year dementia risk score in individuals with mild cognitive impairment (MCI) based on variables collected in routine clinical care. Methods The prediction score was trained and developed using data from the National Alzheimer's Coordinating Center (NACC). Selection criteria included aged 55 years and older with MCI. Cox models were validated externally using two independent cohorts from the Prospective Registry of Persons with Memory Symptoms (PROMPT) registry and the Alzheimer's Disease Neuroimaging Initiative (ADNI) database. Results Our Mild Cognitive Impairment to Dementia Risk (CIDER) score predicted dementia risk with c‐indices of 0.69 (95% confidence interval [CI] 0.66–0.72), 0.61 (95% CI 0.59–0.63), and 0.72 (95% CI 0.69–0.75), for the internally validated and the external validation PROMPT, and ADNI cohorts, respectively. Discussion The CIDER score could be used to inform clinicians and patients about the relative probabilities of developing dementia in patients with MCI.